Neuromodulation Treatments of Pathological Anxiety in Anxiety Disorders, Stressor-Related Disorders, and Major Depressive Disorder: A Dimensional Systematic Review and Meta-Analysis - Gay, Florian; Singier, Allison; Aouizerate, Bruno; Salvo, Francesco; Bienvenu, Thomas C. M. (Frontiers in Psychiatry, 2022)
Background: Pathological anxiety is responsible for major functional impairments and resistance to conventional treatments in anxiety disorders (ADs), posttraumatic stress disorder (PTSD) and major depressive disorder (MDD). Focal neuromodulation therapies such as transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS) and deep brain stimulation (DBS) are being developed to treat those disorders. Methods : We performed a transdiagnostic systematic review and meta-analysis to assess the evidence of the efficacy of TMS, tDCS and DBS in reducing anxiety symptoms across ADs, PTSD and MDD (pre-registered protocol: PROSPERO CRD42021233084). Reports were identified through systematic searches in PubMed/Medline, Scopus and Cochrane library (inception to November 2020), followed by review according to the PRISMA guidelines. Controlled clinical trials examining the effectiveness of brain stimulation techniques on generic anxiety symptoms in patients with ADs, PTSD or MDD were selected. Results: Nineteen studies (RCTs) met inclusion criteria. Overall, focal brain activity modulation was associated with greater reduction of anxiety levels than controls (SMD: -0.48 (95% CI, -0.80 to -0.15), I2=71%). Subgroup analyses revealed positive effects for tDCS across disorders, and of focal neuromodulation in generalized anxiety disorder, PTSD and MDD. Rates of clinical response and remission were higher in the active conditions. However, the risk of bias was high in most studies. Conclusions: There is moderate quality evidence for the efficacy of neuromodulation in treating pathological anxiety.